THE EFFECT OF ONLINE COUNSELING THROUGH VIDEO TELECONFERENCE IN IMPROVING OF KNOWLEDGE OF ORAL AND DENTAL HEALTH IN CHILDREN - Shera Aisya Henry; Prima Agusmawanti; Erna Dwi Agustin (Jurnal Medali, 2022)
Background: Caries is a illness in the hard tissues of teeth that begins with a physiological process of plaque formation and within a certain period of time. Caries was caused by a lack of knowledge to maintain dental & oral health. One of several ways to increase knowledge of dental and oral health is through counseling. Throughout COVID-19 pandemic, counseling was done by online to keep health protocols. The purpose of research is to discover the impact of online counseling through video teleconference.Method: The study uses a Pre-Experimental concept with One-Group Pre-Test and Post Test. The sample was obtained by total sampling technique, which is all fourth and fifth grade students at Islamic Elementary School of Sultan Agung 1 and Sultan Agung 3 Semarang, which met the inclusion criteria and totaled 86 children. Data were obtained from test result and then the data were analyzed using the non-parametric: Wilcoxon Signed Ranks Test.Result: According to data analysis that already implemented, there is a significant distinction (p <0.05) from data beforw & after implementation of online counseling, which means there’s an influence on online counseling because there is an increase in outlook after online counselling.Conclusion: The conclusion obtained is that online counseling through video teleconference has an effect on increasing child’s insight about oral and dental health.